Omega-3 fatty acids: multi-target mechanisms and therapeutic applications in neurodevelopmental disorders and epilepsy - Li, Miao; Li, Zhiqiang; Fan, Yuying (Frontiers in Nutrition, 2025)
Neurodevelopmental disorders (NDDs), including attention deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD), and Tourette's syndrome (TS), impair brain development and function, primarily affecting cognition, behavior, and social skills in children. Epilepsy, characterized by recurrent seizures due to neuronal hyperexcitability, shares pathological mechanisms with NDDs, such as neuroinflammation, synaptic dysfunction, and oxidative stress. Omega-3 fatty acids—primarily docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA)—exert neuroprotective and neuromodulatory effects in these conditions through multifaceted mechanisms. Omega-3 fatty acids play a role in activating the Nrf2/ARE pathway, protecting neurons from oxidative damage, regulating the gut-brain axis, and regulating the balance of microflora. Although Omega-3 fatty acids have a natural safety advantage in improving NDDs and epilepsy symptoms, the bioavailability is limited by the source, formulation form, and dietary environment. Current studies point out that monotherapy has a limited effect and requires a combination of vitamin D, probiotics, or drugs, as well as the development of innovative functional foods to improve intake efficiency. This review summarizes the multi-pathway roles of Omega-3 fatty acids in NDDs and epilepsy, emphasizing the potential as a core component of integrated treatment strategies. Future studies should prioritize precision nutrition approaches and functional food development to optimize patient outcomes in neuropsychiatric care.